Student Evaluations in 8th Grade Science Subjects: Attitude, Self-Efficacy, Gender - Ernawati, M. Dwi Wiwik; Yusnidar, Yusnidar; Kurniawan, Dwi Agus; Rahman, Adriyan Ardi (Jurnal Pendidikan Indonesia, 2022)
The 21st century learning paradigm does not only focus on understanding the learning material, but places more emphasis on thinking, attitude, and communication skills. This study aims to analyze the differences and the relationship between attitudes and self-efficacy of junior high school students. This research uses quantitative methods with associative and comparative research types. The populations in this study were students of grade VIII Junior High School. Determination of the sample is done by using purposive sampling technique. The sample in this study amounted to 72 students. The data collection process was carried out using instruments in the form of attitude and self-efficacy questionnaires. Data were analyzed descriptively and inferentially. The inferential analysis used was the t-test, which was preceded by a prerequisite analysis test, namely the normality test of the data distribution and the homogeneity of variance test. The results showed that there were differences between attitudes and self-efficacy of male and female students. In addition, this study also shows a relationship between the attitude variables and self-efficacy of male and female students. In this case, it is evidenced by a significance value that is in accordance with the existing view.